Assessment of E-Business Transformation and Business Process Reengineering for a SME using Simulation Modelling - Choong, Sarah Shiow Yen (2010)
As globalization takes place, there are increasing opportunities for SMEs to expand their business in a more global market place. With the advancement of ICT, the adoption of E-Business as a business expansion strategy will allow SMEs to break away from the traditional business model, hence providing them with the competitive advantage over their competitors. Although E-Business adoption via BPR is widely used by MNE in developed countries, organization structure, culture, business capacities, economic development, ICT infrastructure and user acceptance of developing countries such as Malaysia SMEs do differ from MNE. This may indicate that not every approach that is deemed successful for MNE will be suitable for SMEs adoption. Therefore, to allow and promote the adoption of E-Business for Malaysian SME, this exploratory research was designed and aimed to offer a proposal of a new business process that involves in the adoption of E-Business for a Malaysian SME company. The method used to accomplish this was by using simulation modelling to project and forecast the potential benefits of the overall BPR project. Before embarking on redesigning efforts, organization culture, E-Business readiness and business change models, was examined to ensure the applicability to the case study. The overall primary and secondary data revealed potential positive outcomes and returns for E-Business adoption via BPR for this Malaysia SME case study. The research findings shows that by adopting BPR as the redesigning methodology from initialization to redesigning phase by using simulation modelling, potential tangible and intangible benefits was able to be forecast by this change efforts. Furthermore by using simulation modelling as a means of mapping out the case study company‟s business processes by documenting the “as-is” model and the proposal of the “to-be” E-Business process model, had allowed more in-depth discussion and findings to be revealed. Based on the findings and recommendations, Malaysia SMEs in similar industry and background may examine these approaches in their business strategy for E-Business adoption.